The making of an ecologist : my career in Alaska wildlife management and conservation - Klein, David R. (University of Alaska Press, 2019)
This is an innovative and collaborative life history of one of Alaska's pioneering wildlife biologists. David R. Klein has been a leader in promoting habitat studies across wildlife research in Alaska, and this is his first-hand account of how science and biological fieldwork has been carried out in Alaska in the last sixty years. This book tells the stories of how Klein did his science and the inspiration behind the research, while exposing the thinking that underlies particular scientific theories. In addition, this book shows the evolution of Alaska's wildlife management regimes from territorial days to statehood to the era of big oil. The first portion of the book is comprised of stories from Klein's life collected during oral history interviews, while the latter section contains essays written by Klein about philosophical topics of importance to him, such as eco-philosophy, the definition of wilderness, and the morality of hunting. Many of Klein's graduate students have gone on to become successful wildlife managers themselves, in Alaska and around the globe. Through The Making of an Ecologist, Klein's outlook, philosophy, and approach toward sustainability, wildlife management, and conservation can now inspire even more readers to ensure the survival of our fragile planet in an ever-changing global society.